From high‐efficiency n‐type solar cells to modules exceeding 20% efficiency with aluminum‐based cell interconnection. (6th November 2012) - Merkle, Agnes; Schulte‐Huxel, Henning; Blankemeyer, Susanne; Feilhaber, Ilka; Bock, Robert; Steckenreiter, Verena; Kajari‐Schroeder, Sarah; Harder, Nils‐Peter; Brendel, Rolf
ABSTRACT We present the integrated development of back‐contacted solar cells and an adequate module interconnection for a high‐efficiency photovoltaic module. We report on a large area (125 × 125) mm2 back‐junction back‐contact n‐type solar cell metallized with aluminum having a total area conversion efficiency of 20.7%. To transfer the high conversion efficiency to the module, we use the laser welding process named aluminum‐based mechanical and electrical laser interconnection for module integration of these back‐contacted solar cells. We further analyze the impact of the busbars of our back‐junction back‐contact cells on the cell performance and report on optimization of the cell/module interface. The new cells have an adapted rear‐side geometry by omitting the emitter busbar. A proof‐of‐concept module consisting of these cells is presented. Copyright © 2012 John Wiley & Sons, Ltd.